2018
DOI: 10.4102/safp.v60i4.4908
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the reasons women give for choosing legal termination of pregnancy at Soshanguve Community Health Centre, Pretoria, South Africa

Abstract: Background: Termination of pregnancy (TOP) is one of the most commonly performed gynaecological procedures in the world and was legalised in South Africa in 1996 with the passing of the Choice on Termination of Pregnancy Act, 1996 (Act No. 29 of 1996). Utilisation of the TOP service increased significantly after the promulgation of the Act, to the extent that 7% of pregnant women in South Africa chose to terminate their pregnancies legally in 2012. Worldwide, women most commonly state their reasons for choosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Results from previous studies, such as an exploration amongst Australian women, support this complex and "thoughtful" nature of reproductive decision making (21). Previous quantitative and qualitative studies (21,36,37), including those from various African settings (12)(13)(14)20,26), similarly found that nancial factors, feeling unready for motherhood, not wanting (more) children, the threat of losing educational and employment opportunities, and partner-relationship problems were important reasons for terminating a pregnancy. While the impact of family dynamics has arisen in previous research (21,25), most emphasis tends to be on the impact of the partner.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Results from previous studies, such as an exploration amongst Australian women, support this complex and "thoughtful" nature of reproductive decision making (21). Previous quantitative and qualitative studies (21,36,37), including those from various African settings (12)(13)(14)20,26), similarly found that nancial factors, feeling unready for motherhood, not wanting (more) children, the threat of losing educational and employment opportunities, and partner-relationship problems were important reasons for terminating a pregnancy. While the impact of family dynamics has arisen in previous research (21,25), most emphasis tends to be on the impact of the partner.…”
Section: Discussionmentioning
confidence: 77%
“…Qualitative explorations of the decision-making process towards termination, while scarcer, seem to align on the complexity of women's decisions to terminate a pregnancy (19)(20)(21).…”
mentioning
confidence: 99%
See 2 more Smart Citations